2010
DOI: 10.1007/s11948-010-9214-6
|View full text |Cite
|
Sign up to set email alerts
|

Textual Appropriation in Engineering Master’s Theses: A Preliminary Study

Abstract: In the thesis literature review, an engineering graduate student is expected to place original research in the context of previous work by other researchers. However, for some students, particularly those for whom English is a second language, the literature review may be a mixture of original writing and verbatim source text appropriated without quotations. Such problematic use of source material leaves students vulnerable to an accusation of plagiarism, which carries severe consequences. Is such textual appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
7
0
2
Order By: Relevance
“…Seejuures on plagiaat kujunenud üleilmseks probleemiks kõigil kõrgharidustasemetel. Nii on tuvastatud teistest allikatest pärit viitamata teksti veidi enam kui pooltes uuritud magistritöödes (Eckel, 2011) ning ligi pooltes analüüsitud doktoritöödes (Ison, 2012). Uus-Meremaal tehtud uuringuga leiti, et ligi veerand üliõpilaste esitatud töödest sisaldas plagiaati, kuigi enne oli uuritavatele selgitatud nii plagiaadi olemust kui ka plagiaadi vältimise võimalusi (Walker, 2010).…”
Section: Sissejuhatusunclassified
“…Seejuures on plagiaat kujunenud üleilmseks probleemiks kõigil kõrgharidustasemetel. Nii on tuvastatud teistest allikatest pärit viitamata teksti veidi enam kui pooltes uuritud magistritöödes (Eckel, 2011) ning ligi pooltes analüüsitud doktoritöödes (Ison, 2012). Uus-Meremaal tehtud uuringuga leiti, et ligi veerand üliõpilaste esitatud töödest sisaldas plagiaati, kuigi enne oli uuritavatele selgitatud nii plagiaadi olemust kui ka plagiaadi vältimise võimalusi (Walker, 2010).…”
Section: Sissejuhatusunclassified
“…In particular, [15] highlights the inherent difficulties in making a determination of plagiarism based on simple text matching between cited words and source texts.…”
Section: Introductionmentioning
confidence: 99%
“…Existing scholarship towards citation practices can actually be quite problematic given the number of factors that guide citation practices of novice writers, particularly without adopting a context-specific approach [15] [16] [17] [18]. Novice writers may carry certain distinctive features.…”
Section: Introductionmentioning
confidence: 99%
“…The basic methodology for this study was adapted from an earlier pilot study by this researcher. 43 The author obtained from the ProQuest database company an Excel spreadsheet of all the English language theses and doctoral dissertations with a completion date of 2009 that included the subject heading "engineering" and were available as full text Adobe PDFs in the ProQuest Dissertations and Theses database. This initial spreadsheet included 727 master's theses and 6298 doctoral dissertations.…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, Gilmore et al 25 found that engineering graduate students were less likely to plagiarize in research proposals than students in other science and technology fields. Eckel 43 used Google to search strings of text from 100 engineering master's theses, finding 28 theses with copied sections over 50 words in a row, seven of which had copied more than a page total verbatim. Finally, Vieyra et al, 44 in a follow-up to the Gilmore et al 25 study, looked at plagiarism in 115 graduate research proposals.…”
Section: Literature Reviewmentioning
confidence: 99%